2017
DOI: 10.1142/s0129167x17500033
|View full text |Cite
|
Sign up to set email alerts
|

Maximally Frobenius-destabilized vector bundles over smooth algebraic curves

Abstract: Abstract. Vector bundles in positive characteristics have a tendency to be destabilized after pulling back by the Frobenius morphism. In this paper, we closely examine vector bundles over curves that are, in an appropriate sense, maximally destabilized by the Frobenius morphism. Then we prove that such bundles of rank 2 exist over any curve in characteristic 3, and are unique up to twisting by a line bundle. We also give an application of such bundles to the study of ample vector bundles, which is valid in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…If r > p, Zhao [11,Proposition 2.8] showed that any maximally Frobenius destabilised rank-r vector bundle over an arbitrary smooth projective curve of genus g ≥ 2 in characteristic p > 0 is not semistable. If r = p, then F X * (L ) is a maximally Frobenius destabilised rank-p stable vector bundle for any line bundle L on an arbitrary smooth projective curve X of genus g ≥ 2 in characteristic p > 0 (see [5] and [11]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If r > p, Zhao [11,Proposition 2.8] showed that any maximally Frobenius destabilised rank-r vector bundle over an arbitrary smooth projective curve of genus g ≥ 2 in characteristic p > 0 is not semistable. If r = p, then F X * (L ) is a maximally Frobenius destabilised rank-p stable vector bundle for any line bundle L on an arbitrary smooth projective curve X of genus g ≥ 2 in characteristic p > 0 (see [5] and [11]).…”
Section: Introductionmentioning
confidence: 99%
“…If r = p, then F X * (L ) is a maximally Frobenius destabilised rank-p stable vector bundle for any line bundle L on an arbitrary smooth projective curve X of genus g ≥ 2 in characteristic p > 0 (see [5] and [11]). If r < p, Zhao [11,Proposition 2.14] showed that for any given natural numbers p > 0, g ≥ 2 and r > 0 with r < p and p g − 1, there exists some maximally Frobenius destabilised rank-r stable vector bundle over some smooth projective curve of genus g ≥ 2 in characteristic p. Under the assumption p > r(r − 1)(r − 2)(g − 1), Joshi and Pauly [3] gave a correspondence between maximally Frobenius destabilised L. Li [2] stable vector bundles of degree 0 and dormant operatic loci, and proved the existence of Frobenius destabilised stable vector bundles of rank r and degree 0. Further results about Frobenius destabilised stable vector bundles can be found in [4,6,7] and [8].…”
Section: Introductionmentioning
confidence: 99%